Evaluating a proxy of the local entropy production rate on the solar photosphere. (May 2019) - Viavattene, G; Berrilli, F; Consolini, G; Del Moro, D; Giannattasio, F; Giovannelli, L; Penza, V
Abstract: The evaluation of the entropy production rate on the solar photosphere and its probability distribution are the key issues for studying the non-equilibrium dynamics of the solar convection. The local entropy production rate can be easily evaluated using the vertical heat flux as a proxy, which is given by a product between the line-of-sight velocity and the surface temperature. In this framework, the solar photosphere provides an incomparable laboratory to study turbulent convection in a dissipative non-equilibrium system near a steady state. In this work, we present some preliminary results on statistics of the local entropy production rate via the vertical heat flux, using line-of-sight velocity and temperature maps of the solar photosphere which are extracted from spectro-polarimetric data making use of the Center of Gravity Method and the simple black body radiation law.